An Examination on Youtube Channels as a Means of Production and Reflection of the Value Judgments of Digital Generation - Şener, Sami; Asil, Aylin (Journal of History Culture and Art Research, 2021)
Due to new technological developments in the world, societies have difficulties in protecting and maintaining their own cultural assets. Values ​​transferred to young individuals through family and education can become significantly ineffective due to the incorrect and excessive use of digital information. Thanks to the opportunity to access all kinds of information and data provided by the Internet, communication and interaction between individuals worldwide has accelerated. It is an undeniable fact that different platforms on the internet have an impact on young individuals having different preferences and priorities than the previous generation. Societies, and especially young individuals, have come under the influence of internet culture because they do not have the necessary knowledge, value judgment and moral understanding due to insufficient and ineffective education and acculturation. This article examines the values that ​​young people adopt under the influence of YouTube platforms in a world where digital information is rapidly transforming, and analyzes the differences between traditional and modern understandings. In the article, the positive and negative behavior and thought patterns that Youtube platforms contribute to young generations are evaluated, and how the value judgments of young people are reshaped through Youtube channels in line with the answers given by the followers of some selected Youtube channels.